DIVERSITY IN BOARD OF DIRECTORS' ROLE IN CREATING CORPORATE VALUE THROUGH GROWTH AND REPUTATION: DIVERSITY IN BOARD OF DIRECTORS' ROLE IN CREATING CORPORATE VALUE THROUGH GROWTH AND REPUTATION - Jao, Robert; Mardiana, Ana; Holly, Anthony (Universitas Katolik Indonesia Atma Jaya, 2024)
The purpose of this study is to analyze the effect of board of director diversity (gender and educational background) on corporate growth and reputation, analyze the effect of board of director diversity (gender and educational background), corporate growth, and reputation on corporate value, and analyze the effect of diversity board of directors (gender and educational background) on corporate value mediated by corporate growth and reputation. This study uses a purposive sampling method in sample selection and uses secondary data, namely the corporate's annual reports published by manufacturing companies listed on Indonesia Stock Exchange during 2018-2020 and Corporate Image Index (CII). The number of corporates observed were 26 with a total of 59 data. The analytical method is the path analysis and the Sobel test for the mediation hypothesis testing. The test results show that gender diversity has a significant positive effect on corporate growth and value, and an insignificant positive effect on corporate reputation. Educational background diversity has an insignificant positive effect on corporate growth, a significant positive effect on corporate reputation, and also an insignificant negative effect on corporate value. Corporate growth and reputation have a significant positive effect on corporate value. This study also indicates that growth mediates the effect of gender diversity on corporate value, but the effect of educational background diversity on corporate value shows otherwise. Finally, reputation does not mediate the effect of gender diversity on corporate value, but mediates the effect of educational background diversity on corporate value